Using preferential trade access to promote global development goals: the case of beef and market access to Norway from Namibia and Botswana. Issue 4 (2nd October 2019) - Bennett, Ben; Rich, Karl M.
ABSTRACT: Using market access to achieve developmental aims has long been held as a key tenet of global development policy. Using a case study approach based on interviews along and across the beef value chain between Namibia, Botswana, and Norway, this article addresses the question of whether market access to high-value markets for livestock products has developmental benefits. The costs and benefits of using market access for beef products as a developmental policy tool are identified and the key role played by international meat traders in both upgrading and rent capture discussed.